ANNUAL TREND OF MEDICAL LICENSING CHARACTERISTICS BY DEPRESSION IN ÑUBLE, CHILE 2008-2017 - Alarcon, María; Robles Inostroza, Ivette Fernanda; Gutiérrez Turner, Eduardo; Alarcón Araneda , José David (Horizonte Sanitario, 2021)
Objective: To identify changes in the annual trend (TA) of the characteristics of Medical Licenses for Depression of the National Health Fund in the Ñuble Region, Chile 2008-2017. Materials and Methods: Descriptive and trend study that included 34,467 of these medical licenses registered in the Commission for Preventive Medicine and Disability of the Ministry of Health of the Ñuble Region, according to characteristics in number of licenses, type of license, type of ICD-10 diagnosis, and subsidy paying entity. The results were presented in absolute numbers and percentages. For the change in BP, a Joinpoint regression model was constructed, and the Joinpoint Regression Program, Version 4.7.0.0 software was used. Results: The number of medical leave due to depression increased 152.3% from 2008 to 2017, according to Type of Leave 99.7% was due to common illness or accident, by Type of ICD-10 Diagnosis 50.7% was due to nonspecific depressive episode (F32.9), 71.6% per compensation fund subsidy payer. The Joinpoint model did not identify a change in the TA in the number of medical licenses in the 10 years under study, rather there was a constant increase estimated at 166 licenses (p = 0.122) for each year. Conclusions: FONASA medical licenses for depression are constantly increasing in the Ñuble Region, it is necessary to privilege the promotion and prevention strategies in the new 2017-2025 mental health plan, and that these efforts are reflected in the control of this pathology and in the decrease of this type of medical licenses.